Literature Review: Environmental, Social, and Governance (ESG) - Yunita, Amalia Rizki; Zai, Fajarman; Khohaerudin, Muhamad; Maimunah, Siti; Kusumaningsih, Ani (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to examine developments and empirical findings related to the influence of Environmental, Social, and Governance (ESG) through a literature review. Data were obtained from 30 scientific journal published between 2021 and 2025 and collected through a systematic search using Google Scholar with the help of the Publish or Perish application. A literature review with descriptive analysis was conducted to identify research trends, the most frequently used variables, and patterns in previous empirical findings. The results indicate that most studies report ESG as having an influence on financial performance, firm performance, firm value, profitability, and earnings management. Specifically, 70% of the reviewed studies documented a significant effect of ESG, while 30% reported insignificant results. Financial performance emerged as the most frequently examined dependent variable, followed by firm performance and firm value. These findings suggest that ESG is increasingly viewed as a crucial factor in supporting business sustainability and enhancing investor confidence. Nevertheless, variations in empirical results indicate opportunities for future research to further explore contextual factors that may strengthen or weaken the influence of ESG.